2009
DOI: 10.1128/jcm.00260-09
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Escherichia coli Common Pilus among Diverse Strains of Human Enterotoxigenic E. coli

Abstract: The Escherichia coli common pilus (ECP) is produced by commensal and pathogenic E. coli strains. This pilus is unrelated to any of the known colonization factors (CFs) of enterotoxigenic E. coli (ETEC). In this study, we investigated the distribution and production of ECP among a collection of 136 human CF-positive and CF-negative ETEC strains of different geographic origins. The major pilus subunit gene, ecpA, was found in 109 (80%) of these strains, suggesting that it is widely distributed among ETEC strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 9 publications
4
57
0
2
Order By: Relevance
“…Several reports have previously shown that this gene is highly conserved among the different intestinal and extraintestinal E. coli pathotypes, including commensal strains (4,5,35,36). A recent gene search study with Brazilian aEPEC strains showed that ecpA was present in all strains displaying an LAL pattern on HEp-2 cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have previously shown that this gene is highly conserved among the different intestinal and extraintestinal E. coli pathotypes, including commensal strains (4,5,35,36). A recent gene search study with Brazilian aEPEC strains showed that ecpA was present in all strains displaying an LAL pattern on HEp-2 cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…The ECP, in association with BFP and other adhesins, contributes to the complex multifactorial interaction of EPEC with host epithelial cells (40). The recent demonstrations that ECP is as frequent as the most common colonization factors of ETEC (5), that the majority of EAEC strains produce ECP (4), and that meningitis-causing E. coli strains also elaborate ECP (called Mat in this pathogroup) to form biofilms (24) reinforce the notion that ECP plays a significant role in the biology of this organism and in its interaction with the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to the following antimicrobials was determined by microdilution on the automated Phoenix system: amikacin, aztreonam, cefazolin, cefepime, cefotaxime, ceftazidime, ciprofloxacin, ertapenem, gentamicin, imipenem, levofloxacin, meropenem, nitrofunrantoin, piperacillin + tazobactam, and trimethoprim-sulfamethoxazole. Detecting virulence genes using PCR Primers used for amplification of DNA fragments corresponding to virulence genes iroN, ompTp, hlyF, iss, iutA [4], tsh [17], hlyA, fyuA, papG [14], papC [18] and ecpA [19] are shown in Table 1. Bacterial DNA was amplified using 2.5 µl of supernatant in 12.5 µl of reaction mixture, which contained 1.5 U Taq polymerase (Invitrogen, Carlsbad, USA), 0.2 mM of each deoxynucleotide triphosphate (dNTP, Invitrogen), 2.5 mM MgCl 2 , PCR Buffer 10X (Invitrogen) and the appropriate primers (20 pmol/ µl).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Proteus mirabilis, Salmonella enterica and E. coli, harbour regulatory systems for reciprocal regulation of these traits (Clegg & Hughes, 2002;Li et al, 2001;Ogasawara et al, 2011;Pesavento et al, 2008;Saini et al, 2010;Simm et al, 2004). We have previously described the common and conserved Mat (meningitis-associated and temperatureregulated) fimbria (Pouttu et al, 2001) [also called ECP (E. coli common pilus); Rendó n et al., 2007], which has host cell-adhesive (Avelino et al, 2010;Blackburn et al, 2009;Lasaro et al, 2009;Rendó n et al, 2007;Saldaña et al, 2009) and biofilm-promoting (Lehti et al, 2010) properties, and is a critical colonization determinant for a probiotic E. coli strain in the intestine of the infant mouse (Lasaro et al, 2009). The fimbrillin subunit MatB is an abundant surface protein on meningitis-associated IHE 3034 cells from a biofilm (Lehti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%